The Emergence of a Latin American and Anti-United States Imaginary of Hemispheric Order: From the Pan American Union to the Latin American Union (1880-1913) - Scarfi, Juan Pablo (Revista Complutense de Historia de América, 2013)
On the basis of an exploration of the ideas and careers of three Argentine politicians and intellectuals, such as Gregorio Vicente Quesada, Roque Sáenz Peña and Manuel Ugarte, the article analyzes the emergence of an cultural diplomatic and legal anti-U.S. imaginary in Argentina by the late-nineteenth and early-twentieth century, in the context of the rise of Pan-Americanism and the United States as a hegemonic power in the Americas. The purpose of the paper is to re-examine the ideological origins of Latin American anti-imperialism, revising the assumption according to which the latter was dominated by a cultural and idealistic critique of the United States, and above all emphasizing the importance that the specific discourse of international law and diplomatic history as proposed by the intellectual and political patrician elite had in the formation of such ideology. It also explores the influence of this legal discourse derived from the writings and diplomatic practice of the patrician elite in the formation of Latin American modern anti-imperialism, which was solidly established by the early twentieth century, particularly after the University Reform in Latin America and had in Manuel Ugarte one of its most emblematic figures.
Keywords: Argentina; intellectuals; diplomacy; United States; Pan-Americanism; anti-imperialism; Vicente Gregorio Quesada; Roque Sáenz Peña; Manuel Ugarte.